2017
DOI: 10.1007/s10641-016-0563-0
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia and handling stress effects on pigmentation and monoamines in Arctic charr

Abstract: Stress responsiveness differs between individuals and is often categorized into different stress coping styles. Using these stress coping styles for selection in fish farming could be beneficial, since stress is one main factor affecting welfare. In Arctic charr (Salvelinus alpinus) carotenoid pigmentation is associated with stress responsiveness and stress coping styles. Thus this could be an important tool to use for selection of stress resilient charr. However, anaesthetics seem to affect carotenoid pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…In dominant individuals, telencephalic 5-HIAA/5-HT was positively correlated to spots, and in subordinate individuals, optic tectum 5-HIAA was negatively correlated to spots (Backström et al, 2015c ). Similarly, in another experiment on the effects of anesthetics both optic tectum 5-HIAA and telencephalic 5-HT were correlated to spots, positive and negative respectively, in two different treatment groups (Backström et al, 2017 ). Thus, carotenoid pigmentation in Arctic charr is associated with stress responsiveness and stress coping styles, similar to the case of melanin pigmentation in Atlantic salmon and rainbow trout.…”
Section: Social Signals and Stress—possible Links With Serotoninmentioning
confidence: 82%
“…In dominant individuals, telencephalic 5-HIAA/5-HT was positively correlated to spots, and in subordinate individuals, optic tectum 5-HIAA was negatively correlated to spots (Backström et al, 2015c ). Similarly, in another experiment on the effects of anesthetics both optic tectum 5-HIAA and telencephalic 5-HT were correlated to spots, positive and negative respectively, in two different treatment groups (Backström et al, 2017 ). Thus, carotenoid pigmentation in Arctic charr is associated with stress responsiveness and stress coping styles, similar to the case of melanin pigmentation in Atlantic salmon and rainbow trout.…”
Section: Social Signals and Stress—possible Links With Serotoninmentioning
confidence: 82%
“…The expression of the dopamine receptor 2 (DRD2) gene was up-regulated in the brain of bold zebrafish Danio rerio compared to reactive individuals (Thörnqvist et al, 2019). Furthermore, handling and treatment with anesthetics increased the concentrations of DA metabolites in the telencephalon of Arctic charr Salvelinus alpinus (Backström et al, 2017) comparable with the aforementioned 5-HT levels in stressed rainbow trout. Also NA, which contributes to vigilance and arousal (Singh et al, 2015), has been subject to increased turnover in rainbow trout under stress conditions (Øverli et al, 2001).…”
Section: Introductionmentioning
confidence: 89%
“…In this study, the fish subjected to acute physical stress showed significantly elevated plasma cortisol levels (levels in the NAG group were 1.7-fold those in the CG group). The maximum levels of plasma cortisol in P. argenteus were somewhat lower than those in other fishes, such as the Arctic charr (Backström et al, 2017) and Oncorhynchus kisutch (Talbot et al, 2009). Therefore, low but significant levels of cortisol after stress could suggest that P. argenteus is sensitive to aquaculture treatment stresses and stresses with significant effects on this species.…”
Section: Discussionmentioning
confidence: 71%